PRELIMINARY ASSESSMENT ON AGROBACTERIUM-MEDIATED TRANSFORMATION OF DENDROBIUM BROGA GIANT ORCHID’S PLBS - Uddain, Jasim; Zakaria, Latiffah; Lynn, Chew Bee; Subramaniam, Sreeramanan (Emirates Journal of Food and Agriculture, 2015)
Dendrobium Broga Giant (Dendrobium Bobby Messina × Dendrobium Superbiens) is a newly introducing hybrid orchid in Malaysia. Determination of target explants potentiality is very important before transformation studies. Bacterial chemotaxis and Transient gusA expression studies were conducted on Dendrobium Broga Giant orchid’s PLBs to evaluate the capability of the bacterial-PLBs interaction during transformation process. Agrobacterium tumefaciens showed positive chemotactic response and their attachment to the PLBs whereas E. coli response negatively. Mild wounded PLBs displayed higher Agobacterium motility compared to other treatments. Mild wounded PLBs immersed for 15 minutes on the Agrobacterium suspension (OD600 nm 0.8) and co-cultivated for 2 days in co-cultivation media supplemented with 200μM acetosyringone showed highest transient gusA gene expression in Dendrobium Broga Giant orchid. Hence, we concluded that positive chemotactic responses and transient gusA gene expression ability indicate the Dendrobium Broga Giant orchid PLBs are a potential target explants for Agrobacterium –mediated genetic transformation studies